اتجاهات طلبة اللغة العربية بكليات التربية بنيجيريا نحو استخدام الوسائل التعليمية في تعليم اللغة العربية. دراسة حالة: كليات التربية بجنوب غرب نيجيريا: Attitudes of Arabic language students in the faculties of education in Nigeria towards the use of Instructional Materials in teaching Arabic Language: A Case Study of the Colleges of Education in Southwest Nigeria - bin Man, Saupi; Mustapha, Toyyib Abiodun; Ibrahim, Toyib Biodun (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص هذه الدراسة الكمية هدفت إلى الكشف عن اتجاهات طلبة اللغة العربية بكليات التربية بنيجيريا نحو استخدام الوسائل التعليمية في تعليم اللغة العربية. دراسة حالة: كليات التربية بجنوب غرب نيجيريا، وقد استخدم الباحثون المنهج الوصفي التحليلي، حيث تم بناء الاستبانة لمعرفة اتجاهات طلبة اللغة العربية في كليات التربية بجنوب غرب نيجيريا نحو توفر الوسائل التعليمية ومدى صلاحية استخدامها لتعليم اللغة العربية في كلياتهم، وتكونت الأداة من (30) فقرة، موزعة إلى طلبة قسم اللغة العربية، وقد تم اختيار أفراد عينة الدراسة بالطريقة العشوائية؛ حيث بلغت عدد عينة الدراسة من (182) طالباً وطالبة، كما استخدم الباحثون الرزمة الإحصائية للعلوم الاجتماعية المعرفة بـــ (SPSS Version 12.0) لتحليل البيانات. وقد أظهرت نتائج أن معظم أفراد العينة أي طلبة اللغة العربية بكليات التربية بجنوب غرب نيجيريا وافقوا على أن الوسائل التعليمية المستخدمة المتوفرة في كلياتهم هي، جهاز الرض، وأفلام العرض، والتسجيلات الصوتية، والحاسوب المسودّة باللغة العربية، والفيديو التعليمي، والتلفاز التعليمي، قد حصلت على درجة متوسطة. كما أوضحت أن استخدام هذه الوسائل التعليمية المذكورة في منهج المجلس الوطني لكليات التربية يساعدهم في تعلم اللغة العربية بشكل مناسب وأسرع بدرجة قوية جدا. Abstract This quantitative study aimed to reveal the attitudes of Arabic language students in the faculties of education in Nigeria towards the use of instructional materials in teaching Arabic. A Case study of the Colleges of Education in southwestern Nigeria. The researchers used the descriptive-analytical approach, where a questionnaire was built to know the attitudes of Arabic language students in colleges of education in southwestern Nigeria towards the availability of instructional materials and the validity of using them to teach Arabic in their colleges. The tool consisted of (30) paragraphs, distributed to the students of the Arabic language department. The study sample members were chosen randomly. The study sample consists of (182) male and female students. The researchers also used the statistical package for the social sciences, known as (SPSS Version 12.0) to analyse the data. The results showed that most of the sample members, i.e., students of Arabic language in the colleges of education in southwestern Nigeria, agreed that the instructional materials used in their colleges are TV equipment, presentation films, audio recordings, computer drafts in Arabic, educational video, and educational television. Medium grade. They also made it clear that using these instructional materials mentioned in the curriculum of the National Commission of Colleges of Education helps them learn the Arabic language appropriately and quickly to a very strong degree.